School Learning Practice Program in Improving Pedagogical Competence of Preservice Teachers - Mustofa, Muhammad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
This study examines the evaluation of the learning practice program at school, specifically the practical field experience program organized by the Education Laboratory of the Tarbiyah and Teacher Training Faculty, UIN Sunan Kalijaga Yogyakarta. This program seeks to develop the pedagogical ability of preservice teachers through hands-on experience in the field. This research employed a mixed method, also known as evaluation research. The researchers employed the Context, Input, Process, and Product (CIPP) evaluation model to assess the program's effectiveness. The findings reveal that the practical field experience program improves preservice teachers' pedagogical competence. However, it still requires improvement and development in various areas, including choosing preferred schools/madrasas, implementation time, and the number of teaching practices. The findings of this study show that program participants who adhere to the program receive more expertise in real-world classroom learning practices. In conclusion, this study demonstrates that the practical field experience program at the FITK UIN Sunan Kalijaga Yogyakarta helps develop the pedagogical competence of preservice teachers. However, it requires further improvement and development to improve program quality.